CYBER PROSTITUTION: BERGESERNYA MASALAH SOSIAL KE DALAM RUANG VIRTUAL - Laksono, Puji; Magfiraini, Riska (UNIVERSITAS SEBELAS MARET (UNS), 2014)
The development of Internet technology with social networking hasformed a new society in a virtual form called Cyber Society. In addition toproviding for the good of human life, the impact of this discovery alsoaffects the dark side of human life. Social problems in the real world werealso penetrated into this virtual world. One of the social problems in thereal world that are emerging in the cyber-society is prostitution (cyberProstitution). The problem of prostitution into the real dark side of society,are now beginning to shift to the cyber society. Prostitution itself in the realworld are categorized as immoral act. The practice of prostitution in thereal world, being blocked by the system of values and norms in society. Butin cyber space which is an anarchist society without social control,prostitution can take place freely.Keywords: Cyber Prostitution, Social Problems, Virtual Spaces.